Theoretical basis for evaluation of national economic competitiveness - Chernova, H. (Економічний вісник Донбасу, 2010)
In this article, under review there are the methodological problems of definition of competitiveness, factors that influence the formation of national economic competitiveness, their modification under economic globalization, and also existing methods of evaluation of country’s competitiveness level of economy are examined. Key words: competition, estimation, national economy.